Opto-optical modulator (OOM) for extreme ultraviolet pulses. Issue 7 (January 2020) - Olofsson, A; Simpson, E R; Labeye, M; Camp, S; Ibrakovic, N; Bengtsson, S; Schafer, K J; Gaarde, M B; Mauritsson, J
Synopsis: There is a profound, almost symbiotic relation between electrons and photons. When light interacts with matter the electrons in the material will start to move and oscillate. When a charged particle, such as an electron, oscillates it will act as a dipole and emit light. We utilize this symbiotic relation and extend the control of light to the extreme ultraviolet (XUV) region using the newly developed XUV opto-optical modulator.